Effect of mild gestational diabetes mellitus on histological, ultrastructural, and quantitative morphometric alterations of rat fetal liver - Sahar Ardalan Khales; Asghar Mafinezhad; Masoud Golalipour; Gholamreza Roshandel; Soraya Ghafari; Abdolhalim Rajabi; Mohammad Jafar Golalipour (Iranian Journal of Basic Medical Sciences, 2024)
Objective(s): Gestational diabetes mellitus (GDM), one of the most common metabolic disorders in pregnancy, impacts maternal and fetal health. This study was designed to assess the effects of mild GDM on the histology, ultrastructure, and morphometry of fetal liver tissue.Materials and Methods: In this experimental study, twenty pregnant rats were randomly allocated into control and streptozotocin (STZ)-induced diabetic groups. Mild hyperglycemia was induced by intraperitoneal injection of STZ (40 mg/kg/bw) on the 5th day of gestation. At day 19 of gestation, fetal livers were separated and subjected to histological, transmission electron microscopic, and quantitative morphometric examinations.Results: In the GDM group, PAS staining was positive, revealing scattered eosinophilic inclusions in some hepatocytes. Masson trichrome staining was also positive and showed some fibrous tissue as fine fibers in the portal spaces that extended to the central vein. Reticulin staining in the GDM group was focally positive in the areas of fibrosis and the portal spaces. Ultrastructural examination showed pyknotic nuclei, karyolysis, degranulation and vesiculation of the rough endoplasmic reticulum, and degeneration of mitochondria in the GDM group. The morphometric examination demonstrated that the mean area of hepatocytes was significantly lower in the GDM group than in the control group (P<0.05). Moreover, the mean diameter of the central vein and the density of megakaryocytes were significantly higher in the GDM group than in the control group (P<0.05). Conclusion: Uncontrolled mild GDM induced the histological, ultrastructural and morphometric alterations in the fetal liver.